EFFICACY OF SURGICAL EXCISION COMBINED WITH INTRALESIONAL TRIAMCINOLONE ACETONIDE THERAPY IN EAR KELOID: CASE SERIES - JAIN, SUMIT; BHATI, TUSHAR; BHATTI, DEEPAK J; KUMAR, RAJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Keloids occur due to abnormal wound healing resulting in extension of raised scar tissue beyond its original margins and rarely they regresses spontaneously. The etiology of keloid is still not clear. Cosmetic concerns, pain, erythema, pruritus, paresthesia, and impairment of function are all keloid related symptoms. There is no single effective treatment for keloids. Keloid’s surgical excision in absence of any adjuvant therapy is considered obsolete due to the high recurrence rate. Corticosteroids are also used as adjuncts to surgical excision to prevent a recurrence. In this prospective, interventional, and case series, six subjects with ear keloid were treated for pre-operative three doses of intralesional Triamcinolone acetonide (TA) injection followed by surgical excision and post-operative two doses of Triamcinolone acetonide injection at the scar site. No signs of recurrence were shown in any lesion.